Implementable Fiscal Policy Rules - Martin Kliem; Alexander Kriwoluzky (Verein für Socialpolitik, 2010)
We use a novel procedure to identify fiscal feedback rules for the US: We start by estimating a DSGE model and on that basis compute the Ramsey optimal responses to structural shocks. Then we let the policy maker choose from a general set of rules to match the dynamic behavior of a number of key variables like output, debt, and consumption, in the competitive equilibrium with their corresponding dynamic behavior in the Ramsey equilibrium. In the next step we estimate the model again but employ the contingency derived previously. The policy rules derived are general, not as complex as Ramsey and easily implementable.
Keywords: E62; H30; C51; 330; Fiscal policy; Bayesian model estimation; Global Sensitivity Analysis